Analysis of Marketing Strategy on Financial Performance Through Marketing Performance with Environmental Uncertainty as Moderating Variable in Islamic Banks in Jambi - Sumantri Sumantri; Amri Amir; Tona Aurora Lubis; Rike Setiawati (Dinasti Publisher, 2022)
This study aims to analyze the marketing strategy on financial performance through marketing performance with environmental uncertainty as a moderating variable in Islamic banks in Jambi. The sample in this study was 40 people/respondent, the data analysis technique used SEM-PLS with the help of the SmartPLS application. The findings in this study: 1. There is a positive and significant influence between marketing strategies on the marketing performance of Islamic banks in Jambi Province. 2. There is a positive and significant influence between the marketing strategy on the financial performance of Islamic banks in Jambi Province. 3. There is a Positive and Significant Influence between Marketing Strategy on Marketing Performance Moderated by Environmental Uncertainty of Islamic Banks in Jambi Province. 4. There is a Positive and Significant Influence between Marketing Strategy on Financial Performance Moderated by Environmental Uncertainty of Islamic Banks in Jambi Province. 5. There is a Positive and Significant Influence between Marketing Performance on Financial Performance in Islamic Banks in Jambi Province. 6. There is a Positive and Significant Effect between Marketing Strategy on Financial Performance through Marketing Performance at Islamic Banks in Jambi Province. All research findings have met the conditions that must be met in the SEM-PLS model.